Comentarios a la Constitución Española de 1978 / dirigidos por Oscar Alzaga Villaamil. T.II.. Artículos 10 a 23 / Santiago Sánchez González ...[et al.] - Sánchez González, SantiagoAlzaga Villaamil, Óscar
Referencias bibliográficas